The probiotic Shewanella putrefaciens PDP11 target virulence factors by modulating quorum sensing inhibition - Domínguez-Maqueda, Marta; Llamas, Inmaculada; Moriñigo-Gutiérrez, Miguel Ángel; Balebona-Accino, María del Carmen (My University, 2022)
Bacteria communicate with each other by producing signal molecules and regulating the production of virulence factors that have importance in pathogenicity. Quorum sensing (QS) is a bacterial communication mechanism based on the perception of population density and secretion of determining signal molecules called autoinducers (AI) such as the case of Acylhomoserine lactones (AHLs). AHLs-mediated QS processes seem to be common in the marine environment and among marine pathogenic bacteria, which pathogenesis could be mitigated by probiotics, among others. Probiotics are defined as live microbial cells that confer health benefits to the host and some of their mechanisms include the production of antagonistic compounds that are inhibitory toward pathogens. In this sense, Shewanella putrefaciens Pdp11, a strain described as a probiotic for use in aquaculture, has been analysed to mediate QS processes by quorum-quenching assays using synthetic AHLs. The enzymatic activity is estimated at around 80% and 30% for C8- and C10-HSL, respectively, while the rest of AHLs tested were not degraded by the Pdp11 strain. It would be an interesting feature of the probiotic Pdp11 strain since these AHLs are related to facilitating microbial adhesion by promoting biofilm formation among other virulence factors related to pathogens. On the other hand, a distinctive feature of AHL inactivated by lactonase is that it can be reactivated by acid treatment. In this way, little C8-AHL was recovered when it is extracted to pH2, which indicates the enzyme activity is not derived from the hydrolysis of the lactone ring derived from the action of lactonases, suggesting the enzyme activity in Pdp11 could be an AHL-acylase. The potential QQ activity of Pdp11 was unknown so, these preliminary studies led to a further as another promising probiotic QQ tool for aquaculture.
Keywords: Acuicultura - Bacterias; Shewanella putrefaciens Pdp11; Probiotic; Homoserine lactone; Quorum quenching